Pretreatment of alcoholic extract of Scrophularia Striata on spatial memory and lipid peroxidation in male rats during crystal meth addiction - Somayyeh Hatami; Homeira Hatami; Farzam Sheikhzade; Golamreza Dehgan (Fasa University of Medical Sciences, 2017)
Background & Objective: Crystal meth damages the brain cells by inducing oxidative stress. In the present study the long- term injection effect of alcoholic extract of Scrophularia Striata on spatial memory and lipid peroxidation in male rats during crystal meth addiction was investigated.  Material & Methods: 49 male rats were divided in 7 groups including: control, sham (saline), crystal meth (5 mg/kg), Scrophularia Striata extract (100 and 200 mg/kg), pretreatment of Scrophularia Striata (100 mg/kg) + crystal meth (5 mg/kg), and pretreatment of Scrophularia Striata (200 mg/kg) + crystal meth (5 mg/kg).  Morris water maze test was used for assessing the spatial memory, and Malondialdehyde (MDA) was assayed as an index of lipid peroxidation. One-way analysis of variance (ANOVA) was used to analyze the data. Results: Spatial memory was significantly reduced by Crystal meth (P<0.001). Spatial memory was significantly improved by Scrophularia (100 and 200 mg/kg) in comparison to control group (P<0.05). Pretreatment of Scrophularia in both doses significantly improved the spatial memory in crystal meth group (P<0.05). MDA level significantly increased in crystal meth group (P<0.05), but pretreatment of Scrophularia significantly reduced the elevated level of MDA (P<0.05). Conclusion: It seems that, psychoactive drugs can impair spatial memory by inducing oxidative stress. Pretreatment of Scrophularia as an antioxidant, improves spatial memory which has been reduced by crystal meth.